2020
DOI: 10.3389/fcell.2020.00209
|View full text |Cite
|
Sign up to set email alerts
|

The Small GTPases Rab27b Regulates Mitochondrial Fatty Acid Oxidative Metabolism of Cardiac Mesenchymal Stem Cells

Abstract: Cardiac mesenchymal stem cells (C-MSCs) are endogenous cardiac stromal cells that play a crucial role in maintaining normal cardiac function. Rab27b is a member of the small GTPase Rab family that controls membrane trafficking and the secretion of exosomes. However, its role in regulating energy metabolism in C-MSC is unclear. In this study, we analyzed mitochondrial oxidative phosphorylation by quantifying cellular oxygen consumption rate (OCR) and quantified the extracellular acidification rate (ECAR) in C-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…OCR and ECAR were quantified using Seahorse XF 96 extracellular flux analyzer (Agilent Technologies, Lexington, MA, USA) as previously described with minor modifications (18,19). Briefly, the cells were plated at 10,000 cells/well in the Seahorse XF cell culture microplate.…”
Section: Seahorse Analysis Of Mitochondrial Respirometrymentioning
confidence: 99%
See 1 more Smart Citation
“…OCR and ECAR were quantified using Seahorse XF 96 extracellular flux analyzer (Agilent Technologies, Lexington, MA, USA) as previously described with minor modifications (18,19). Briefly, the cells were plated at 10,000 cells/well in the Seahorse XF cell culture microplate.…”
Section: Seahorse Analysis Of Mitochondrial Respirometrymentioning
confidence: 99%
“…Western blotting was performed as previously described (18,19). Briefly, the protein samples were separated on 10% SDSpolyacrylamide gels, and the gel was then transferred onto nitrocellulose membranes (LI-COR Biosciences).…”
Section: Western Blotting Assaymentioning
confidence: 99%
“…Mitochondrial fatty acid oxidation is the main source of ATP in many tissues and organs [34]. Fatty acid oxidation is a complex biological process involving mitochondrial β-oxidation, tricarboxylic acid cycle activity, and the electron transport chain [35]. Alterations in fatty acid metabolism can contribute to a variety of pathologies and cell dysfunction [36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, treating AD-MSCs with mangiferin, a class of flavonoids extracted from mango, could improve the mitochondrial respiratory function by increasing the expression of mitochondrial OCR and OXPHOS-related proteins, thereby inducing the AD-MSCs to differentiate into brown adipocytes and improve obesity [ 67 ]. Rab27b, a member of the small GTPases family, can increase the OXPHOS in cardiac mesenchymal stem cells (C-MSCs) and significantly reduce mitochondrial glycolysis; consequently, this maintains the fatty acid oxidative metabolism of the C-MSCs, suggesting that regulatory genes and drugs may ultimately play a therapeutic role by affecting the mitochondrial energy metabolism [ 68 ]. However, recent studies have reported that canagliflozin, a therapeutic medicine for type 2 diabetes, can inhibit the activity of glutamate dehydrogenase 1, which interferes with mitochondrial OXPHOS and ATP production; consequently, it inhibits the proliferation and migration of the BMSCs, which may lead to a decline in the tissue repair ability of the transplanted BMSCs.…”
Section: The Role Of Mitochondrial Energy Metabolism In the Regulatiomentioning
confidence: 99%
“…Unlike their differentiated states, the MSCs in their undifferentiated states have low levels of intra-cellular ROS and high levels of antioxidant enzymes [ 79 ]. Studies have reported that excessive ROS levels can impair the osteogenic differentiation ability of the MSCs [ 68 , 80 ]. However, in the adipogenic differentiation of the MSCs, the production and increase in the ROS levels is not only a result of the adipocyte differentiation, but also one of the conditions for the adipogenic differentiation of the MSCs.…”
Section: The Role Of Mitochondrial Energy Metabolism In the Regulatiomentioning
confidence: 99%